Understanding patient perspectives on digital therapeutics and its platform for insomnia: insights from focused group interviews - Jinhyun Kim; Kyung Mee Park; Suonaa Lee; Sooji Park; Minji Hong; Jaeyong Shin; Eun Lee (BMC, 2024)
Abstract Background Digital therapeutics (DTx) is a treatment option that uses computer software to provide evidence-based interventions for medical disorders. DTx platforms are digital services that facilitate interactions among stakeholders of DTx treatment within a standardized structure. However, there is still a lack of overall awareness regarding the effectiveness and usage of DTx and DTx platforms. This study aimed to investigate insomnia patients' recognition, thoughts, feelings, and demands for conventional treatments versus DTx for insomnia. Methods Nine participants, aged 19-50 years, who had experience with professional medical interventions for insomnia, were recruited through purposive sampling. Two online focus group interviews, each lasting 1.5 h, were conducted. The interview questions focused on difficulties encountered during conventional treatment, inadequate recognition of DTx, and concerns and demands regarding DTx and its platform. The data were analyzed using thematic analysis. Results The participants reported subjective difficulties associated with receiving conventional treatment, including concerns about drug side effects and dependence, social stigma, and lack of perceived necessity for treatment. They expressed concerns about DTx, such as cost-effectiveness, evidence on efficacy, and concerns about breach of personal information. Additionally, their demands included convenience of use, reduction in social stigma related to the use of DTx, compatibility of DTx with other healthcare systems, and enhanced communication with healthcare providers when using DTx platforms. Conclusions The focus group highlighted the need for increased awareness, demonstrated efficacy, cost-effectiveness, cybersecurity measures, and accessibility of insomnia DTx and its platforms. Tailored approaches considering patient characteristics are crucial for widespread adoption of insomnia DTx and its platforms.